2002
DOI: 10.1159/000064297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mizoribine on IL-6 Release by Peripheral Blood Mononuclear Cells

Abstract: Background/Aim: A novel immunosuppressant, mizoribine (MZB), has recently been reported to be effective in the treatment of IgA nephropathy (IgAN), although its mechanism of action remains unknown. This study was conducted to investigate whether the efficacy of MZB on IgAN is exerted by suppression of interleukin-6 (IL-6) release. Methods: Peripheral blood mononuclear cells (PBMC) were collected from 4 children with IgAN (median age 13.0 years) and 4 control children (median age 5.2 years). PBMC were cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Thus, it is possible that one of the proteinuria-lowering mechanisms of MMF is mediated through suppression of IL-6 synthesis, which is consistent with its effects in suppressing other cytokines [38]. The pathogenetic role of IL-6 in IgAN is further supported by observations that suppression of IL-6 by mizoribine, a mold extract that also selectively inhibits lymphocyte proliferation, improves glomerular lesions in childhood IgAN and in ddY mice, a rodent model of IgAN [47][48][49]. In addition, MMF has been shown in animal models of subtotal renal ablation to possess direct anti-inflammatory and antiproliferative effects that attenuate macrophage and T-cell infiltration [50], and reduce interstitial myofibroblast infiltration and collagen deposition [51].…”
Section: Discussionmentioning
confidence: 87%
“…Thus, it is possible that one of the proteinuria-lowering mechanisms of MMF is mediated through suppression of IL-6 synthesis, which is consistent with its effects in suppressing other cytokines [38]. The pathogenetic role of IL-6 in IgAN is further supported by observations that suppression of IL-6 by mizoribine, a mold extract that also selectively inhibits lymphocyte proliferation, improves glomerular lesions in childhood IgAN and in ddY mice, a rodent model of IgAN [47][48][49]. In addition, MMF has been shown in animal models of subtotal renal ablation to possess direct anti-inflammatory and antiproliferative effects that attenuate macrophage and T-cell infiltration [50], and reduce interstitial myofibroblast infiltration and collagen deposition [51].…”
Section: Discussionmentioning
confidence: 87%
“…We recently demonstrated that MZB significantly suppressed the IL‐6 release from peripheral blood mono­nuclear cells in vitro and suggested that this action played some role in the clinical efficacy of MZB on IgAN 26 …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Mizoribine could suppress IL-6 release in vitro and may exert its efficacy on IgA nephropathy [ 34 ]. Mizoribine was able to inhibit the spontaneous production of IL-6 by fresh rheumatoid synovial cells (RSC) in a dose–response fashion [ 35 ].…”
Section: Discussionmentioning
confidence: 99%